(3GdeYLe GdeTJed Ydi CSeGA GdTjhN GdfHds - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYdfG ef NjQ Gdedc s
(3QJH CSeGA GdTjhN Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B254 s
Keywords: (3GdJGQjNs